Development of recurrent pressure ulcers, risk factors in older patients: a prospective observational study. (1st April 2020) - Arisandi, Defa; Ogai, Kazuhiro; Urai, Tamae; Aoki, Miku; Minematsu, Takeo; Okamoto, Shigefumi; Sanada, Hiromi; Nakatani, Toshio; Sugama, Junko
Abstract : Objective: Prevention of recurrent pressure ulcers (PU) is one of the most important challenges in wound care, furthermore, the risk factors for recurrent PUs are still not fully understood. This study aimed to explore the risk factors for recurrent PU development within two weeks, including biophysical skin properties, pro-inflammatory cytokine (tumour necrosis factor [TNF]-α) levels and bacterial species, in older patients. Method: This prospective study was conducted in a long-term care facility with patients whose PU had healed within two months. Biophysical skin properties were evaluated by stratum corneum hydration, pH, sebum content and transepidermal water loss. TNF-α level was measured using skin blotting. Skin bacteria were collected using tape stripping and determined by species-specific gene amplification. These parameters, along with Braden scale and interface pressure, were evaluated every two weeks for a total period of eight weeks. A penalised generalised estimating equation analysis was used to determine the risk factors for recurrent PUs. Results: In total, 20 patients were included in this study, with 57 observations. Of these, recurrent PU was seen in eight observations. Elevation of pH (p=0.049; odds ratio [OR] per 1 unit=3.91, 95% confidence interval [CI]:1.01–15.15), presence of Acinetobacter spp. (p=0.039; OR versus culture-negative=6.28, 95%CI:1.10–35.86) and higher interface pressure (p=0.008; OR per 1 mmHg=1.06, 95%CI:1.01–1.10) on the healed PU were significantly related to the development of recurrent PU. Conclusion: Higher pH, existence of Acinetobacter spp. and higher interface pressure on the site of the healed PU were associated with the development of recurrent PUs in older patients undergoing conservative treatments.